Content-Based Filtering Recommendation System Using Categories Search Engine - Vicky Rolanda; Teddy Surya Gunawan; Wanayumini (International Journal of Research in Vocational Studies (IJRVOCAS), 2023)
The search function is often used with certain keywords, usually using keywords and also catagories, someone knows what they want to search for, but some people often search according not to what they want to find but what is recommended to be seen based on ratings that can be by categories. Based on the recommendation system that is often applied, it is often developed based on the similarity between one item and another. So, this time the author wants to develop a search by users based on the same category so that users can reduce their desire to search according to the category they want, in this paper the author uses a recommendation system based on content base filtering.